How can corporate social responsibility activities create value for stakeholders? A systematic review - Peloza, John; Shang, Jingzhi (Journal of the Academy of Marketing Science, 2011)
Corporate social responsibility (CSR) activities have the potential to create stronger relationships between firms and stakeholders. Although marketing researchers have studied the impacts of CSR activities on stakeholder responses, the CSR activities and outcomes measured have been varied and inconsistent. In this article we (a) review the extant literature to outline which CSR activities and outcomes have been included in previous research; (b) synthesize the means by which CSR activities can add value for consumers and how these have been represented in CSR literature, and; (c) present a research agenda for future research to allow greater consistency among CSR researchers.